Causes of hospital admission of chronic kidney disease patient in a tertiary kidney care hospital - Imtiaz, Salman; Qureshi, Ruqaya; Hamid, Amna; Salman, Beena; Drohlia, Murtaza F; Ahmad, Aasim (Journal of Clinical Nephrology, 2019)
Background: Patients with chronic kidney disease (CKD) are at the risk of increase hospital admission as compared to the general population, due to various reasons. They have increased vulnerability to cardiovascular diseases (CVD) as well as infections, therefore they usually got admit in health care units due to various reasons. The causes of hospitalization in CKD patients in this part of the world are not studied well. Methods: This cross sectional study was conducted in The Kidney Centre Post Graduate Training Institute (TKC-PGTI) of Karachi. Variables included in the study were age, gender, are of residence, ethnicity, smoking status and level of education. Comorbid conditions like causes of CKD and causes of hospitalization. Data analysis performed by using software IBM SPSS 21. Results: Total of 269 patients were enrolled in our study. The male 148(55%), mean age was 55 years. The most common cause of hospitalization in our population was infection148 (55%) and urinary tract infection (UTI) was the most common site of infection 55 (20%) followed by sepsis of unknown origin 29(10.8%). Cardiovascular events like volume overload 32 (11.4%) and acute coronary syndrome 20(7.4%) were the second most important cause of hospitalization. Conclusion: Hospitalization of CKD patients is high, and in our population infection is found to be the leading cause of hospital admission. Infection originating from urinary tract is more common in all stages of CKD patients, while blood born infection originating from double lumen (DL) dialysis catheter or arteriovenous fistula (AVF) cannulation is more common in dialysis population. Cardiovascular events, both acute coronary syndrome and pulmonary edema due to volume overload followed the infections.